Precision Agriculture through Nutrient Correction for Sustainable Development suing Wireless Sensor Network - Flores, Kristoffer (Archīum Ateneo, 2019)
With the conversion of lands that are supposed to be used for agriculture, food supply is becoming a major problem in the Philippines. Improvement in the production and efficiency in agriculture are the most promising solution to this threat in food supply through precision agriculture. This study implemented precision agriculture particularly nutrient correction to improve agricultural production in the Philippines. A wireless sensor network composed of soil sensors that monitored moisture, temperature and electrical conductivity, light and humidity was implemented. A PID Controller was used to generate a recommended amount of fertilizer to the farmer. Using the sensor data and Recurrent Neural Network, soil was also characterized which were used by the user to simulate possible soil health management in terms of frequency of application of fertilizer. A website-based graphic user interface was created for easy access by the user.